Social participation, gender, and well-being in older adults: insights from Malaysian active ageing index study - Abdullah, Siti Farra Zillah; Hui, Foh Foong; Chai, Sen Tyng; Mutang, Jasmine Adela (Universiti Malaysia Sabah (UMS), 2024)
This study establishes a social participation index among older adults in Malaysia, utilising data from the nationwide project, "Development of an Active Ageing Index for Malaysia." The study employed multistage cluster simple random sampling, that included 800 respondents from Selangor, Terengganu, Sabah, and Sarawak. The social participation domain encompasses four indicators: (i) voluntary activities; (ii) caregiving for children/grandchildren; (iii) caregiving for the infirmed and disabled; and (iv) political participation. The social participation index scored 22.8. The most common participation involved "care for children and grandchildren," followed by "care for the infirmed and disabled," "political participation," and finally "voluntary activities." Females showed a significantly higher contribution to "care for children and grandchildren" compared to males. Then, more males reported attending meetings of trade unions, political parties, or political action groups, as well as contacting politicians or public officials, compared to females. Moreover, those who engaged in weekly "care and/or education of grandchildren" reported significantly higher well-being. Similarly, individuals who attended trade union, political party, or political action group meetings, or contacted politicians or public officials in the past year, had significantly higher well-being compared to those who did not engage in these activities. This study highlights the ongoing potential for older adults to make meaningful contributions to society, particularly in grandparenting-related activities. Furthermore, there is a clear need for innovative enrolment programs aimed at encouraging voluntary activities among older individuals within the local community. Lastly, the paper addresses several significant implications arising from the study's findings.